High-intensity physical performance parameters in soccer - Ortega, Daniel Rojano; Martín Simón, Miguel Ángel (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. High-speeds distances covered during a soccer match are considered a good indicator of team success, especially for some playing positions. These distances vary markedly among different playing positions, and match congestion typically results in a reduction of high-intensity activities. However, the different playing levels might influence those results. Aim of Study. 1) To analyze the differences in the total distance covered during the match, and the high-intensity physical performance parameters between the various playing positions in the four highest-ranking teams in the 2018 FIFA World Cup. 2) To follow the evolution of those parameters throughout the competition. Material and Methods. Match data, reported by FIFA, of the four teams classified for the semi-finals in the 2018 World Cup were used. Differences between the different playing positions and the different phases were analyzed. Results. The distances covered at high speeds and the number of sprints performed during a soccer match may differentiate team performance. The distance covered at 20-25 km/h, at speeds exceeding 25 km/h, and the total number of sprints were significantly lower (p < 0.05) for central defenders; they were higher for the wide-midfielders, though not significantly likely due to the low sample size. No significant differences were observed between the different phases in most of the study variables. Conclusions. Understanding the differences between the different playing positions in the highestranking teams of the competitions may help coaches to carefully design players’ rotations and include different soccer-specific drills for each playing position to contribute to team success. Together with a good technical and tactical strategy, promoting post-match recovery may be the key for team success.
Keywords: recovery; sprints; high running speed; congested; matches